Investigating mood-modification, withdrawal, and sensitization in compulsive sexual behaviour - Sassover, Eli; Kushnir, Talma; Weinstein, Aviv M. (Frontiers in Psychiatry, 2024)
Background and aims Compulsive Sexual Behaviour (CSB), defined as a persistent failure to control repetitive sexual impulses, has been discussed as a pathological phenomenon for centuries. Various terms, such as excessive sexual behaviour, hyper-sexuality, compulsive sexual behaviour disorder (CSBD), or sexual addiction (SA), have been used to describe it, contributing to ongoing debates about its theoretical framework. The following three studies aim to empirically assess whether CSB exhibits key elements of behavioural addiction (mood-modification, sensitization/tolerance, and withdrawal). Method Three studies, involving participants with and without CSB, were conducted. The mood-modification hypothesis was tested by exposing participants to short films inducing positive, negative, and emotionally neutral moods, followed by an evaluation of their craving for pornography. To test the sensitization hypothesis, participants viewed short films with varying levels of explicit sexual stimuli, and their level of actual wanting and liking were assessed through self-reports. For the withdrawal hypothesis, participants underwent a 10-day sexual abstinence, with self-reports of various symptoms, collected on pre-intervention, 3rd, 7th, and 10th days. Results Contrary to previous studies of addiction, CSB participants didn’t show increased craving to mood induction and negative mood actually decreased craving for pornography. Secondly, they showed wanting to explicit sexual stimuli although it was not increased with explicitness. Finally, they demonstrated reduced withdrawal symptom during abstinence. Conclusion The results of this study provide conflicting results concerning the model of behavioural addiction. There is supporting evidence for wanting in response to explicit pornography stimuli although it was not associated with increased explicitness. There is also evidence for reduced withdrawal during abstinence. Finally, there was no evidence that mood modification increases craving for pornography, negative mood actually decreased craving. Further research is needed to test the various models of CSB.